Customer Perception of curry powder brands with special reference to Mohanlal’s Taste Buds brand - S. Kurup, Vishnu; Poulose, Daly (Recent Research in Science and Technology, 2017)
This study was conducted to understand the customer perception about various curry powder brands with special reference to Mohanlals curry powder brand and also to understand the effectiveness of AD campaigns and to analyse how effectively these campaigns lead to brand recall. A survey was conducted among women and was oriented towards understanding the various attributes which they consider for choosing a curry powder brand for purchase. The majority of the respondents were from the region of Cochin and the survey included a sample size of 50 respondents. The sample was selected randomly from among a group of house wives and working women in Kerala and hence the process of simple random sampling was adopted. One of the key findings was that Eastern curry powder brand is the most preferred brand when various attributes were taken into consideration and also an analysis of the favorite curry powder brand was done. Only 8% of the total respondents suggested MTB as their favorite brand and this is a very small number when compared to Eastern. The major drawback of MTB as inferred from the study was poor marketing and advertising campaigns which affected brand recall. One of the key findings was that promotional offers were fewer in the case of curry powder brands and hence these brands should come up with more promotional offers to maintain a sound customer base. Secondly, quality and taste are the most important attributes preferred by customers in choosing curry powder brands. So, curry powder brands should maintain and upgrade these key attributes for ensuring customer satisfaction.